CONCEPT MAPPING THEORY OF POLITICAL SCIENCE USING BIBLIOGRAPHIC ANALYSIS - Muhammad Syaifuddin; Suswanta Suswanta; Misran Misran; Syamsul Bahri Abd. Rasyid (JWP (Jurnal Wacana Politik), 2021)
Politics is a discipline of science that is part of social science. What distinguishes political science from other social sciences is the object studied. The development of research on the theory of political science and politics becomes a question in this paper. Topic mapping and topic classification based on keywords, countries, and themes discussed were the main focus of this research, including visual density based on keywords, showing the level of saturation political science theory. In this study, the data used were data that had been downloaded from the Scopus database with several limitations to limit and be more specific to the results of the discussion. After the documents to be reviewed and analyzed are bibliographical using the VOSViewer and NVivo 12 Plus software, the data is exported .CSV and .RIS formats. This study aims to provide insights into subsequent research on the theory of political science